E-Modul Pembelajaran Menulis Esai Berbasis Problem Based Learning untuk Perguruan Tinggi - Diyan Permata Yanda; Dina Ramadhanti (Universitas Muhammadiyah Jember, 2024)
This article aims to describe the learning product in the form of an e-module for learning to write essays based on problem-based learning. This e-module was prepared with the hope of being able to answer the needs of learning to write essays, that learning to write requires teaching materials that are appropriate to student's learning needs and to foster students' independence in writing essays. With problem-based learning, students are expected to be able to write essays based on problems that are close to their daily environment. This research is development research with a 4D model, namely: definition, design, development, and distribution. After validation, evaluation, and revision, this e-module was declared valid, practical, and effective. This learning e-module is declared suitable for learning to write essays. By using problem-based learning, students can write based on problems, conduct investigations, develop and present problems in an essay, and evaluate solutions to problems presented in an essay.